Neuropeptide S receptor ligands: a patent review (2005-2016). (4th March 2017) - Ruzza, Chiara; Calò, Girolamo; Di Maro, Salvatore; Pacifico, Salvatore; Trapella, Claudio; Salvadori, Severo; Preti, Delia; Guerrini, Remo
ABSTRACT: Introduction : Neuropeptide S (NPS) is a 20-residue peptide and endogenous ligand of the NPS receptor (NPSR). This receptor was a formerly orphan GPCR whose activation increases calcium and cyclic adenosine monophosphate levels. The NPS/NPSR system is expressed in several brain regions where it controls important biological functions including locomotor activity, arousal and sleep, anxiety, food intake, memory, pain, and drug addiction. Areas covered : This review furnishes an updated overview of the patent literature covering NPSR ligands since 2005, when the first example of an NPSR antagonist was disclosed. Expert opinion : Several potent NPSR antagonists are available as valuable pharmacological tools despite showing suboptimal pharmacokinetic properties in vivo . The optimization of these ligands is needed to speed up their potential clinical advancement as pharmaceuticals to treat drug addiction. In order to support the design of novel NPSR antagonists, we performed a ligand-based conformational analysis recognizing some structural requirements for NPSR antagonism. The identification of small-molecule NPSR agonists now represents an unmet challenge to be addressed. These molecules will allow investigation of the beneficial effects of selective NPSR activation in a large panel of psychiatric disorders and to foresee their therapeutic potential as anxiolytics, nootropics, and analgesics.